The Effects of Kinesio Taping with LASER Therapy to Improve on Pain Threshold, Blood Flow, and Balance Ability in Patient with Knee Osteoarthritis - Kim, Kyung-Hun; Kim, Dong Hoon (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2021)
Objective We investigated the effects of Kinesio Taping with Laser Therapy (KTLT) on the Pain threshold, Blood flow, and Balance ability of patients with Knee Osteoarthritis.Methods A total of 32 patients were randomly divided into KTLT and Control (CON) group. KTLT group was performed 30 min three times a week for four weeks in low-level laser therapy (LLLT) treatment process with Taping. CON group performed 30 min three times a week for four weeks in sham LLLT treatment process with sham taping. To measure the oppressive pain threshold, Commander Algometer and for the measurement of the blood flow rate of the skin surface, a noninvasive approach, Laser Doppler imaging equipment was used and the standing balance ability test was performed by Center of Pressure (COP), Limited of Stability (LOS).Results There was a significant difference (P<0.05) between before and after training in both groups, and KTLT group showed significant improvement in both groups.Conclusions In this study, we confirmed KTLT on the Pain threshold, Blood flow, and Balance ability of Patient with Knee Osteoarthritis.
Keywords: Osteoarthrose; Physiotherapie; Rehabilitationserfolg; Rehabilitationsmanagement; Schmerz